TAHAP-TAHAP BERPIKIR DALAM PEMBUKTIAN DENGAN INDUKSI MATEMATIKA DITINJAU DARI TEORI BERPIKIR SWARTZ - Allen Jesica; Santi Irawati; Abdur Rahman As'ari (Jurnal Kajian Pembelajaran Matematika, 2021)
The subjects in this research were asked to solve problems while expressing their thoughts think aloud. An interview was conducted to explore deeper thinking processes. The written data and verbal data obtained were reviewed and analyzed based on Robert Swartz's theory of the thought process which included four stages, namely, generating ideas, explaining ideas, assessing the appropriateness of ideas (assessing). the reasonableness of ideas), and complex thinking (complex thinking). The results of the validation of the assignment sheet instruments and the interview instruments used in this study obtained very valid criteria. From the results of the research, it can be explained that S1 constructs proof with mathematical induction completely and correctly.